ANALISIS PERBANDINGAN CITRA MEREK KECAP ABC DENGAN KECAP BANGO PADA PEDAGANG KULINIER DI PASAR TRADISIONAL KABUPATEN SUKOHARJO - Zailani, Abdullah (JURNAL ILMIAH EDUNOMIKA, 2024)
As the soy sauce industry continues to grow and competition becomes more intense, many companies are using brand approaches as marketing strategies, thereby enhancing product marketing with brand power that influences consumer behavior. The purpose of this research is to identify and test the differences between the brand image of ABC soy sauce and the brand image of Bango soy sauce among culinary traders. This research was conducted in the traditional market of Sukoharjo Regency. The population consists of culinary business actors who use Bango brand soy sauce and ABC brand soy sauce. The sample consisted of 80 traders using the purposive sampling technique, specifically 40 traders of culinary businesses using Bango soy sauce and 40 traders of culinary businesses using ABC soy sauce. The research results concluded that there is a difference in the image of ABC soy sauce compared to Bango soy sauce among culinary traders in the traditional market of Sukoharjo Regency.Keywords: brand image, soy sauce, culinery